Economy of Photosynthate Use in Nitrogen-fixing Legume Nodules: Observations on Two Contrasting Symbioses - Layzell, David B. (1979)
The economy of C use by root nodules was examined in two symbioses, Vigna unguiculata (L.) Walp. (cv. Caloona):Rhizobium CB756 and Lupinus albus L. (cv. Ultra):Rhizobium WU425 over a 2-week period in early vegetative growth. Plants were grown in minus N water culture with cuvettes attached to the nodulated zone of their primary roots for collection of evolved CO(2) and H(2). Increments in total plant N and in C and N of nodules, and C:N weight ratios of xylem and phloem exudates were studied by periodic sampling from the plant populations. Itemized budgets were constructed for the partitioning and utilization of C in the two species. For each milligram N fixed and assimilated by the cowpea association, 1.54 ± 0.26 (standard error) milligrams C as CO(2) and negligible H(2) were evolved and 3.11 milligrams of translocated C utilized by the nodules. Comparable values for nodules of the lupin association were 3.64 ± 0.28 milligrams C as CO(2), 0.22 ± 0.05 milligrams H(2), and 6.58 milligrams C. More efficient use of C by cowpea nodules was due to a lesser requirement of C for synthesis of exported N compounds, a smaller allocation of C to nodule dry matter, and a lower evolution of CO(2). The activity of phosphoenolpyruvate carboxylase in nodule extracts and the rate of (14)CO(2) fixation by detached nodules were greater for the cowpea symbiosis (0.56 ± 0.06 and 0.22 milligrams C as CO(2) fixed per gram fresh weight per hour, respectively) than for the lupin 0.06 ± 0.02 and 0.01 milligrams C as CO(2) fixed per gram fresh weight per hour. The significance of the data was discussed in relation to current information on theoretical costs of nitrogenase functioning and associated nodule processes.